Still watching?: A study on the post-adoption switching intention of Netflix subscribers in Metro Manila, Philippines using the perspective of the push-pull-mooring Framework - The moderating roles of age, household size, and income - Baello, Juliana Kelly S. (Animo Repository, 2023)
The adoption and competition of Over The Top (OTT) Services have constantly been increasing. However, Netflix has been facing decreasing membership subscriptions. Through this study, the researchers focused on several factors that may influence the switching intention of Netflix subscribers, and the Push-Pull-Mooring model was utilized to understand this behavior. The researchers employed a quantitative research method and conducted quantitative data analysis through descriptive statistics, inferential statistics, and moderation analysis. An online survey questionnaire was conducted wherein a total of 402 valid responses were collected through purposive sampling. Thus, the study’s findings reveal that the push, pull, and mooring factors significantly impact the switching intention of Netflix subscribers in Metro Manila, Philippines. As for the moderating variables, age did not affect the relationship of push, pull, and mooring factors with switching intention. Likewise, household size did not moderate the relationship of pull and mooring with switching intention. However, household size positively affected the push factor and switching intention. For income, the results revealed that it had influenced the push, pull, mooring factors, and switching intention. With these results, Netflix, OTT platforms, and the like may use this paper to understand the industry better. Furthermore, future researchers may conduct a similar study on OTT platforms or specific generations to increase the data on this topic.